Cancer and lymphatic marker FOXC2 drives wound healing and fibrotic tissue formation - Granoski, Maia B.; Fischer, Katharina S.; Hahn, William W.; Sivaraj, Dharshan; Kussie, Hudson C.; Quintero, Filiberto; Alsharif, Abdelrahman M.; McKenna, Eamonn; Yasmeh, Jonathan P.; Hostler, Andrew C.; Mora Pinos, Maria Gracia; Erickson, Robert P.; et al. (Frontiers in Physiology, 2024)
The FOXC2 transcription factor has been tied to a wide range of disease states, serving as a promising prognostic biomarker associated with aggressive basal-like human breast cancers (increased cancer invasion and metastasis). Dysregulation of FOXC2 expression has also been found to promote defects in lymphatic remodeling and hyperplastic lymphedema-distichiasis (LD). Since chronic lymphedema is a forerunner of several malignancies and cancers have been known to arise from poorly healing chronic wounds (e.g., Marjolin ulcers), we examined the effect of Foxc2 dysfunction on skin wound healing. We used our splinted excisional wounding model that mimics human-like wound healing on wildtype and Foxc2 +/- mice (n=4), which demonstrate incomplete lymphatic vasculature and lymphatic dysfunction. Wound size was measured over the course of 18 days. Tissue was explanted from both groups at post-operative day (POD) 14 and 18 and stained with Masson’s Trichrome to assess scar formation, Picrosirius Red for dermal integrity, or immunofluorescence to assess lymphatic (LYVE1) cell populations. Wildtype mice completely healed by POD 14, while Foxc2+/- mice did not completely heal until POD18. Scar area of healed Foxc2+/- mice (POD 18) was larger than that of healed wild-type mice (POD 14; p=0.0294). At POD 14, collagen fibers in the scars of Foxc2+/- mice to be narrower (p=0.0117) and more highly aligned (p=0.0110), indicating significantly more fibrosis in these mice. Collagen fibers in both groups became longer (p=0.0116) and wider (p=0.0020) from POD 14 to 18, indicating a temporal evolution of fibrosis. Foxc2+/- mice also had lower numbers of LYVE1+, F4/80+ and CD4+ cells compared to wildtype mice. Individuals over 65 years old are more likely to develop cancer and are highly susceptible to developing chronic wounds. Here, we found that FOXC2, which is tied to cancer metastasis and lymphatic dysregulation, also impairs wound healing and promotes fibrotic tissue architecture. With FOXC2 proposed as a potential therapeutic target for cancer metastasis, its downstream systemic effects should be considered against the increased chance of developing nonhealing wounds. Further delineation of the microenvironment, cellular events, and molecular signals during normal and Foxc2-associated abnormal wound healing will improve clinical therapies targeting this important marker.